Effect of corrosion on the tension behavior of painted structural steel members. (June 2017) - Kim, In-Tae; Dao, Duy Kien; Jeong, Young-Soo; Huh, Jungwon; Ahn, Jin-Hee
Abstract: The long-term structural performance of steel structures can be directly related to corrosion. In this study, tensile tests were conducted on corroded steel members to examine the effect of corrosion damage on their tensile behavior. For this purpose, tension specimens were manufactured using the members of a 75-year-old painted steel bridge exposed to the marine environment. The corroded surfaces of the tension specimens were measured using an optical 3D digitizing system to obtain their residual thicknesses. After the tensile tests were performed, the characteristics of the tensile behavior of the corroded steel plates such as the yield load, ultimate load, and elongation were evaluated quantitatively. An effective thickness has been suggested using the mean and standard deviations of the residual thicknesses of the specimens. This can be used to evaluate the tensile strength of a structural steel member with an irregularly corroded surface. The practical measurement intervals for taking the various thickness measurements of the corroded steel members are also presented. Highlights: Tensile strength test of structural member with local corrosion under atmospheric corrosion environments Measurement of corroded surfaces using an optical 3D digitalizing system Examination of tensile behavior of the corroded specimens Suggestion of effective thickness for evaluating the tensile strength using mean and standard deviation of residual thickness